Organized Crime in the Corruption of Garuda Indonesia's Former Director (Analysis of the Jakarta District Court Decision) - Sari, Merina Puspita; Nata, Akbar Raga (Nursyam Centre, 2023)
This article delves into the complex world of organized crime and traces the historical roots of its development and impact on society. Focusing on corruption cases involving PT Garuda Indonesia and Rolls Royce the transnational dimensions of organized crime are examined. A criminological lens helps dissect the structural elements of organized crime to uncover networks of clients who seek to exploit legal loopholes. International legal mechanisms such as the UN Convention against Transnational Organized Crime aim to standardize responses to this widespread threat. Examining corruption within this framework highlights the global reach of organized crime and the need for collective action. Lastly as society grows the challenges of organized crime also increase. Global understanding combined with international cooperation guided by legal frameworks is essential to combat the complex and widespread nature of organized crime. This case study highlights the importance of criminology in identifying and combating the problem of organized crime in an interconnected world by underscoring the urgent need to address not only individual crimes but also their interconnectedness.